Consistent Recruitment in a Graded Manpower System - Davies, G. S. (Management Science, 1976)
A manpower system is examined in which the members are organized according to rules frequently met in graded firms and industries. We determine the manpower structures possible under such conditions and specify the form of the recruitment distribution, given an initial structure.